2017
DOI: 10.3390/md15060166
|View full text |Cite
|
Sign up to set email alerts
|

Borrelidins C–E: New Antibacterial Macrolides from a Saltern-Derived Halophilic Nocardiopsis sp.

Abstract: Chemical investigation of a halophilic actinomycete strain belonging to the genus Nocardiopsis inhabiting a hypersaline saltern led to the discovery of new 18-membered macrolides with nitrile functionality, borrelidins C-E (1-3), along with a previously reported borrelidin (4). The planar structures of borrelidins C-E, which are new members of the rare borrelidin class of antibiotics, were elucidated by NMR, mass, IR, and UV spectroscopic analyses. The configurations of borrelidines C-E were determined by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…The structures of compounds 4 – 7 were readily identified as borrelidin A ( 4 ), borrelidin CR1 ( 5 ), borrelidin E ( 6 ) and borrelidin K ( 7 ) on the basis of comparisons of HR‐ESI‐MS, 1 H‐NMR, 13 C‐NMR data with those reported previously ( Figure ) …”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The structures of compounds 4 – 7 were readily identified as borrelidin A ( 4 ), borrelidin CR1 ( 5 ), borrelidin E ( 6 ) and borrelidin K ( 7 ) on the basis of comparisons of HR‐ESI‐MS, 1 H‐NMR, 13 C‐NMR data with those reported previously ( Figure ) …”
Section: Resultsmentioning
confidence: 81%
“…The borrelidins have attracted significant attention from the natural products community, and their noteworthy anti‐infective and cytotoxic activities have especially drawn the interest and efforts of biosynthetic and chemical synthesis researchers . In this study, three new borrelidins ( 1 – 3 ), along with four previously reported family members ( 4 – 7 ), were isolated from a likely associated symbiont S. olivaceus SCSIO LO13 from the marine pulmonated mollusk Onchidium sp.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Further borrelidins (C-E) have been reported from the genus Nocardiopsis, displaying cidal effect, particularly against the Gram-negative pathogen Salmonella enterica, and moderate cytotoxicity against the SNU638 and K562 carcinoma cell lines. [27] Further new borrelidins F-I, but also, they were toxic, have been reported from mangrove-derived Streptomyces sp. [28] Ferulic acid.…”
Section: Identification and Importance Of The Obtained Secondary Metamentioning
confidence: 99%
“…For instance, lajollamycin was isolated from the new strain Streptomyces nodosus [6], while salinosporamide A and borrelidins C-E were obtained from Salinispora tropica [13] and Nocardiopsis sp. [14], respectively. ese compounds are now a special target of several biotechnological industrial and academic institutions, since they possess a strong potential to be developed into pharmaceutical products [15].…”
Section: Introductionmentioning
confidence: 97%